PENGARUH ERGONOMIC EXERCISE TERHADAP KADAR PIRAI PADA LANSIA DI POSBINDU DESA X WILAYAH KOTA TULUNGAGUNG - Dewi Zuniawati (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Elderly people are susceptible to increased uric acid levels or gout due to a decrease in the function of purine metabolism in the body due to degenerative factors. One action that can be taken to reduce uric acid levels is physical activity. Ergonomic exercise is physical activity with a combination of muscle movements and breathing techniques. This research uses a Quasy Experiment research design. The population in this study were all elderly people in Posbindu Village X with a total of 46 respondents. The sample for this research was some of the elderly in Posbindu Village X with a total of 30 respondents selected using purposive sampling techniques. Research instruments: observation sheet and operational standard sheet. Data processing takes the form of editing, coding, scoring, tabulating, and data analysis using the non-parametric Wilcoxon sign rank test. The results of this research show that before the ergonomic exercise was carried out, the majority of respondents who had high levels of gout, with 23 respondents (77%) experienced a decrease in distribution to 7 respondents (23%). The ρ value (0.001) < α (0.05). This research proves that there is an influence of ergonomic exercise on gout levels in the elderly in Village.